Alpha Errors, Beta Errors and Negative Trials - Desmond Leddin (Canadian Journal of Gastroenterology)
Reports of negative trials arc increasing in number as standard therapy for many gastrointestinal diseases is refined. The validity of a negative report depends on the number of patients in the trial, the alpha and bern error and the difference in efficacy which the trial is able to detect. The relationship between these parameters is discussed and a formula given for the calculation of trial size. All reports of negative trials should include not only the number of patients involved and the level of significance of the results but also the beta error and the detectable difference in efficacy of the treatments.